QUO VADIS ONLINE JOURNALISM: PREDICTING THE FUTURE OF PRINT MEDIA AND ONLINE MEDIA - Supadiyanto Supadiyanto (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
Now online journalism into a new chapter in the world of journalism. Paper technology increasingly frozen out by the internet technology. Various press company went bankrupt, whether at home or abroad. So they divert business to the online media. Because it is considered faster, environmentally friendly and efficient. The implication, glory newspaper and other paper-based media increasingly replaced by internet-based online media presence.And proven, now the internet had transformed the conventional industry, a digital-based industry. One was the mass media industry. Until now the mass media still believed to be the most powerful tool in influencing public opinion. Industry print media, electronic media and online media growing rapidly today, confirms the mass media business is a much-loved business entrepreneurs. The trend now, the expansion of the conventional mass media towards online internet-based media more lively. Advantages of online media is far superior in speed display, the content more varied and wide range power, the whole audience can be accessed all over the world, and are economically very cheap, makes a lot of print media company's management to change its format to online media. As it is, online journalist to be very prospective, economic calculation and idealism. Especially now everyone can be a journalist online. The term popular, everyone can be a journalist resident (citizen journalism). By being an online journalist, everyone is more extensive and flexible reporting in a variety of activities. Finally, the competition between online media becomes a necessity that cannot be avoided anymore. Only online media, supported by editorial management and professional management of corporations, eventually became the winner in the heat of the media industry (print, electronic and online media).Unfortunately, public preparedness in the country in the use of online media as a medium of information, entertainment, education and supervision, is still questionable. The majority of Indonesia's population are still not aware of the media, strengthen public awareness of how the use of print media, especially online media is still quite low. That is the challenge that must be answered by all elements of the nation. By optimizing the use of online media and make everyone become a journalist or citizen journalism online and will accelerate national development.